Entrepreneurship and crafts: a review of the literature from a resource and capabilities-based theory - Ruiz-Carta, Erika P. (EFIM Ediciones, 2021)
The handicraft sector continues to be one of the most important for the economic growth of many countries, therefore the creation of companies or entrepreneurship in this sector becomes relevant both in theoretical and practical terms. In this framework, it is necessary to study which are those elements that within the entrepreneurship in the artisan sector can generate competitive advantages, that is why from the theory of the Theory Based on Resources and Capabilities (VBR) a review of the literature is proposed to determine the sources of competitiveness of the businesses in this sector. Thus, scientific publications with high impact and empirical evidence are used to analyze the proposed phenomenon and determine that training for managers as well as human talent are key components for the artisan sector, in this sense, the discussion associated with offering training to artisan enterprises in these areas is proposed in order to consolidate one of the most important sources of economic growth for many countries and from there begin to build better economic conditions for its inhabitants.